Mixed solvent system as binder for the production of silicified microcrystalline cellulose‐based pellets. Issue 36 (7th May 2019) - Ting, Grace Loong; Chan, Yen Yee; Chaw, Cheng Shu
ABSTRACT: Silicified microcrystalline cellulose pellets with hydroxypropyl methylcellullose (HPMC) as modifier were prepared using a mixed solvent as liquid binder. Pellets were produced using extrusion‐spheronization with a mixed solvent consisting of water and isopropanol as liquid binder. The key spheronization aid was Prosolv® SMCC 90. Low viscosity grade HPMC was incorporated aiming to modify release of indometacin. Physical characteristics including breaking load, apparent density and flow properties, particle size distribution and shape were determined. Drug loaded pellets were also tested for dissolution profiles. By adjusting liquid binder property, at isopropanol to water ratio of 3.5 to 6.5, pellets of desirable size and shape with reasonable yields were obtained. Pellets exhibited good flow property and they were mechanically strong. Pellet with higher HPMC content displayed a faster drug dissolution profile. This was because low viscosity grade HPMC was not enough to create strong gel. Instead hydration of HPMC molecules increased matrix's hydrophilicity and weakened the structure of pellet faster. The release of indometacin was partly based on the erosion of hydrated matrix. The presence of HPMC in the pellets would require a mixed solvent to produce desirable shape. Incorporation of HPMC had modified drug release from the pellets without further coating. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47924. Abstract : Transformation of wet mass into extrudes then to pellets